2008
DOI: 10.1111/j.1540-4560.2008.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Postconflict Reconciliation: Intergroup Forgiveness and Implicit Biases in Northern Ireland

Abstract: Even after a conflict has formally ended, there is still a need for postconflict reconciliation and the building of mutual forgiveness and trust between communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 33 publications
(40 reference statements)
7
105
0
5
Order By: Relevance
“…Researchers have considered perceived threat and lack of trust as central determinants of intergroup conflict and prejudice (Dovidio, Gaertner, Kawakami, & Hodson, 2002;Stephan & Renfro, 2002;Riek et al, 2006;Tam et al, 2008). However, a growing body of research has shown that positive contact with outgroup members can reduce threat perceptions (Pettigrew, Christ, Wagner, & Stellmacher, 2007; and increase outgroup trust (Hewstone, Cairns, Voci, Hamberger, & Niens, Mediated Moderators of Extended Contact 6 2006;Tam, Hewstone, Kenworthy, & Cairns, 2009;Tausch et al, 2007).…”
Section: The Mediating Role Of Threat and Trustmentioning
confidence: 99%
“…Researchers have considered perceived threat and lack of trust as central determinants of intergroup conflict and prejudice (Dovidio, Gaertner, Kawakami, & Hodson, 2002;Stephan & Renfro, 2002;Riek et al, 2006;Tam et al, 2008). However, a growing body of research has shown that positive contact with outgroup members can reduce threat perceptions (Pettigrew, Christ, Wagner, & Stellmacher, 2007; and increase outgroup trust (Hewstone, Cairns, Voci, Hamberger, & Niens, Mediated Moderators of Extended Contact 6 2006;Tam, Hewstone, Kenworthy, & Cairns, 2009;Tausch et al, 2007).…”
Section: The Mediating Role Of Threat and Trustmentioning
confidence: 99%
“…Intergroup contact, under the appropriate conditions, may increase positive intergroup emotions and enhanced empathy, as well as reduce negative emotions such as anxiety (Pettigrew & Tropp, 2006Tam et al, 2008). Contact improves intergroup relations by enhancing knowledge about the out-group and reducing perceived threat and apprehension regarding meeting members of the other group.…”
Section: Contact Between Groupsmentioning
confidence: 99%
“…Selected mainstream intergroup frameworks currently exist, for example intergroup emotions (e.g. Mackie & Smith, 2002) and intergroup forgiveness (Moeschberger, Dixon, Niens, & Cairns, 2005;Tam, et al, 2008Tam, et al, , 2007Philpot & Hornsey, 2008), that certainly could prove to be relevant for the promotion of peaceful coexistence. Future studies could unveil not only how narrative templates of historical intergroup transgressions within the Hindutva ideology implicate adverse intergroup emotions, but also if and how these could be reduced by intergroup forgiveness.…”
Section: Development and Operationalisation Of Context-sensitive Measmentioning
confidence: 99%